SAT0003 Single-nucleotide polymorphisms associated with P2X7R function regulate the onset of gouty arthritis. (15th June 2017) - Tao, J; Cheng, M
Abstract : Background: Gout is an inflammatory disease, considered to be caused by the increased production of IL-1β stimulated by monosodium urate (MSU) crystals. However, some hyperuricemia patients, even gouty patients with tophi in the joints, never have gout attack, indicating some other pathogenic pathways participating in the secretion of IL-1β rather than MSU in the pathogenesis of acute gouty arthritis. ATP-P2X7R-IL-1β axis may be one of them. Objectives: The purpose of this study is to explore the role of ATP in the pathogenesis of gout, and the association between ATP receptor (P2X7R) function associated single nucleotide polymorphisms and gout arthritis. Methods: The non-synonymous SNPs loci of P2X7R in Chinese people were screened, to compare the frequencies of different alleles and genotype distribution of selective SNPs in 117 gouty patients and 95 hyperuricemia patients. Then peripheral white blood cells were purified from the peripheral blood of randomly selected 43 gout patients and 36 hyperuricemia patients from the total. After culturing the cells with MSU or MSU+ATP, supernatants were collected and the concentrations of IL-1β were detected by enzyme linked immunosorbent assay (ELISA). Results: 1. Eight SNPs loci including rs1653624, rs10160951, rs1718119, rs7958316, rs1621388, rs16950860, rs208294, rs17525809 and rs2230912 were screened and detected, and rs1653624, rs7958316 and rs17525809 were demonstrated associated with gout arthritis. 2. After the stimulation with MSU+ATP, the concentrations of IL-1β in supernatants of gouty patients were significantly higher than that in hyperuricemia groups [(131.08±176.11)pg/ml vs (50.84±86.10)pg/ml]. Furthermore, gouty patients carrying susceptibility genotype AA or AT of rs1653624 had significant higher concentration than that carrying non-susceptibility genotype TT [(104.20±164.25)pg/ml vs (21.90±12.14)pg/ml]. However, no differences were found while stimulated with MSU alone. Conclusions: ATP promotes the pathogenesis of gouty arthritis by increasing the secretion of IL-1 β, and its receptor (2X7R) function associated single nucleotide polymorphisms may be related to gouty arthritis, which indicates that ATP-P2X7R signaling pathway plays a significant regulatory role in the pathogenesis of gout. Acknowledgements: This study was sponsored and funded by the Anhui Provincial Natural Science Foundation (1708085MH191) and grants from the National Natural Science Foundation of China (81671601). Disclosure of Interest: None declared